IbM Implementation of SRI Method in Semi Organic Rice Farm in Pasarean Village, Pamijahan Subdistrict, Bogor District - . Hastuti; Ahyar Ismail; Dea Amanda; Arini Hardjanto; Fitri Dewi Raswatie (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Most rice farmers in Pamijahan Subdistrict cultivate in traditional way and have relatively low income. Farmer’s low income was caused by low productivity so farmer welfare also decrease. Traditional methods in cultivation also affect the environment because of high usage of chemical fertilizer. This community service program aims to increase farmer’s income in Pamijahan Subdistrict by introducing System of Rice Intensification (SRI) method using organic fertilizer. The main activities are: instituional strengthening, SRI training and cultivation practice (pilot project). The expected outcome of this community service activity is to increase production by using less input and to get higher selling price for organic rice. There are four steps in this program is: planning, organizing, actuating and controlling. The sequence is: 1) Program preparation, consist of: program socialization, institutional strengthening, cooperation with SRI trainer, preparation of experimental field, seed and agricultural equipment; 2) Institutional strengthening with rice farmer; 3) SRI method training with trainers from Nagrak Organic SRI Center to change farmer’s mindset and train farmers about SRI cultivation method; 4) Cultivation in experimental field (650 m2), where farmers practice to cultivate rice with SRI method; 5) Experimental field harvesting, unhuled rice yielded around 65 kg or 30–40 kg of rice; and 6) Supervision during the experimental cultivation by IPB lecturers and village officials.